Mass Biosynthesis of Coumestrol Derivatives and Their Isomers via Soybean Adventitious Root Cultivation in Bioreactors - Lee, Eun Jung; Song, Myoung Chong; Rha, Chan-Su (Frontiers in Plant Science, 2022)
Coumestrol (CMS) derivatives are unique compounds, which function as phytoalexins; they are derived from soybean roots, following abiotic and biotic stresses. As a phytoalexin, CMS forms a defense system that enables plants to maintain their viability. However, it is still challenging to achieve the mass production of phytoalexins, which exhibit pharmacological values, via plant breeding. Here, the synthesis of CMS derivatives from the seedling, plant, and adventitious root (AR) of Glycine max were investigated under artificial light, as well as via a chemical elicitor treatment. In the presence of constant light, as well as under treatment with methyl jasmonate, the CMS monoglucoside (coumestrin; CMSN) and malonyl CMSN (M-CMSN) contents of the AR culture (four weeks) increased drastically. The two CMS derivatives, CMSN and M-CMSN, were obtained as a mixture of isomers, which were identified via nuclear magnetic resonance analysis. These derivatives were also observed in a soybean plant that was grown on artificial soil (AS; five weeks) and a Petri dish (nine days) although in considerably lesser quantities than those observed in the AR culture. Compared with the two other media (AS and the Petri dish), the AR culture achieved the superior synthesis of CMSN and M-CMSN within a relatively short cultivation period (less than one month) in laboratory-scale (3 L) and pilot-scale (1000 L) bioreactors. The isoflavone content of AR under the constant light conditions was three-fold that under dark conditions. Significant quantities of malonyl daidzin and malonyl genistin were produced in the root of AS and the seedling of Petri dish, respectively. Flavonol glycosides were not produced in the AR culture under the dark and light conditions, as well as in AS under the dark condition. However, significant contents of kaempferol glycosides were produced in the leaves of AS and seedling of Petri dish, following the light treatment. Thus, we proposed that the established soybean AR-cultivation approach represented a better method for biosynthesizing phytoalexins, such as the CMS derivatives, as plant-derived functional materials.